Estudo de propriedades de filmes de óxidos anódicos crescidos em diferentes eletrólitos ácidos sobre o biomaterial Ti-50Zr at.% - Ferreira, Elivelton Alves (2008)
Studies on the influence of the nature of the growth electrolyte on the properties of oxide films grown on the Ti-50Zr at.% alloy were carried out. The results obtained through the different measurements done (chronoamperometry, open circuit potentials, and reconstruction rates) showed that phosphate incorporation into the matrix of oxide films grown in H3PO4 make them unstable, bringing a greater dissolution compared to the ones grown in CH3SO3H, H2SO4, and HNO3. The electrochemical impedance spectroscopy measurements showed that the phosphate incorporation into the oxide films grown on the Ti-50Zr at.% alloy by different methods and thickenesses lead to high values of electrical resistance when compared with the ones of films grown in CH3SO3H, H2SO4, and HNO3. The nature of the growth electrolyte was observed to also affect the semiconducting properties of the different oxide films grown on the alloy, leading to different voltammetric profiles of these films when illuminated with radiation of energy greater than that of the band gap. The studies on the effect of the exchange of the electrolyte solution in the galvanostatic growth of anodic films in two steps showed that the breakdown potentials are dependent on the nature of the electrolyte. On the other hand, these measurements also revealed that the initial electrical breakdown of the film or the nature of the electrolyte in which it was initially grown do not alter the film growth kinetics during the second step, carried out in another electrolyte.